Foreign direct investment and the robustness of host-country commitment - Shaikh Shahnawaz (Review of Economic Analysis (REA), 2022)
This paper presents a model of a forward-looking government wooing foreign direct investment by enacting policies that reflect its commitment to the foreign enterprise. The ease with which the government is able to spend or carry out economic reform to complement the foreign venture evolves over time and influences the likelihood of its sustained commitment. The domestic and external strength of the government, the stability and not necessarily the level of returns from the project, venture-specificity of government spending or reform, and public and elite attitudes toward foreign commercial entry determine how invested the government remains in the long term success of the enterprise. More committed governments tend to be stronger and prefer robust investor-regime relationships. Reform that is not designed too narrowly to favor the investor is also less likely to be reversed later. Like pro-FDI public sentiment, a noisy policy environment induces deeper government commitment.
Keywords: F20; F21; O24; 330; FDI; Policy reform; Strength of government